Fibrous Dysplasia versus Juvenile Ossifying Fibroma: A Dilemma - Sreelakshmi N. Nair; Raghavendra Kini; Prasanna Kumar Rao; Gowri P. Bhandarkar; Roopashri Rajesh Kashyp; Manjunath Rai; Neel Naik; Athul Santhosh (Case Reports in Dentistry)
Fibrous dysplasia (FD) is a condition characterized by excessive proliferation of bone forming mesenchymal cells which can affect one bone (monostotic type) or multiple bones (polyostotic type). It is predominantly noticed in adolescents and young adults. Fibrous dysplasia affecting the jaws is an uncommon condition. The most commonly affected facial bone is the maxilla, with facial asymmetry being the chief complaint. The lesion in many instances is confused with ossifying fibroma (OF). Diagnosis of these two lesions has to be done based on clinical, radiographic, and microscopic findings. Here, we present a case of fibrous dysplasia of maxilla in a nine-year-old boy mimicking juvenile ossifying fibroma.